Examining Climate Change Perception and Coping Mechanisms in Coastal Communities of Bangladesh - Noman, Abu Saleh Mohammad; Quaisar, Mohammad Mahbub; Akhter, Nargis (Journal of Posthumanism, 2025)
Climate change flounces a significant challenge to Bangladesh for concentration of hard core poor people in its coastal areas where a cogent number of livelihoods exclusively rely on climate sensitive sectors, face high exposure to climate change induced calamities and develop very vulnerable coping strategies to it. The study examines the climate change perception of coastal community of Bangladesh, explores their experiences of climate change impact at their national and local level and looks into their coping mechanisms. The study perused that a substantial number of coastal people heard about the concept of climate change. The climatic impact they heard most is cyclone and damage of infrastructure. The prime source of hearing is private TV channels. The coastal communities are affected most by cyclone in autumn and summer and tidal surge in late autumn. They adopt highly vulnerable coping mechanisms with the impacts of climate change. It is very unprecedented that as major coping strategy to cyclone they stay home to keep houses strong instead of going to cyclone shelters.